(3QSGFd aj Yde GdJhMjO hGdJUhas - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj , (B1143 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI ; gPg eSGFd aj Yde GdJhMjL ddTjN YHO GdZfj GdfGHdSj hGdMeO ddg QH GdYGdejf CeG HYO agPg eSGFd aj Yde GdJhMjO hGdJUha EPG GJab GdCeQ hSCd YfgG jYLR YfgG CcHQ Uhaj eObb aj Yde GdJhMjO hGdJUhas
(3BNQgG (B:s
(3hjbQC GdaGJLI hjgOjG Edi LejY ENhGfge ef GdeDefjf hGdeSdejf hGdeSdeGJ GdCMjGA efge hGdCehGJ hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 32s
(3eYLe GdeDdajf (B2 / 176s
(3Sdc GdOQQ (B3 / 30s
(3gOjI GdYGQajf (B1 / 590s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds